2018
DOI: 10.18805/ijar.b-858
|View full text |Cite
|
Sign up to set email alerts
|

Combined supplementation of organic acid blend and hydrolyzed yeast mixture increases growth performance and tibia bone strength in broilers

Abstract: This study investigates the effects of hydrolyzed yeast mixture (HYM) and an organic acid blend (OAB) supplementation individually and in combination on growth performance and tibia bone characteristics of broilers. A total number of 128 one day- old chicks were divided into four different groups with each group having 4 replicates in a trial of 35 days. The first group was kept as control whereas, the second and third groups were given HYM and OAB respectively. The fourth group (HYM+OAB) was given combination… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 13 publications
1
3
0
Order By: Relevance
“…Currently we lack sufficient literature to explain the effects of different levels of garlic and ginger supplementation on weight of visceral organs. Bursa of fabricius, thymus and spleen are parts of immune system and an increased weight of these organs is an indicator of immunological advances as they produce lymphocytes which protect birds from the harmful effects of invading pathogens (Saleem et al, 2018a). Our study confirms earlier findings of Rahimi et al (2011) who reported no difference in weight of pancreas and spleen after supplementation of birds with ginger.…”
Section: Resultssupporting
confidence: 90%
See 3 more Smart Citations
“…Currently we lack sufficient literature to explain the effects of different levels of garlic and ginger supplementation on weight of visceral organs. Bursa of fabricius, thymus and spleen are parts of immune system and an increased weight of these organs is an indicator of immunological advances as they produce lymphocytes which protect birds from the harmful effects of invading pathogens (Saleem et al, 2018a). Our study confirms earlier findings of Rahimi et al (2011) who reported no difference in weight of pancreas and spleen after supplementation of birds with ginger.…”
Section: Resultssupporting
confidence: 90%
“…Bone problems are among the major health issues of fast growing birds and can adversely affect production performance and profitability of birds if not taken care of properly (Vashan et al, 2016). Higher value of tibiotarsal index is an indicator of higher mineralization and higher strength of bone, whereas, higher robusticity index indicates poor mineralization and bone strength (Saleem et al, 2018a). In our study supplementation of garlic and ginger increased bone strength as both of these phytobiotics enhance the absorption of minerals in feed by improving the morphology and microbiology of intestine (Eltazi, 2014) that leads to better mineralization of bone giving it more strength.…”
Section: Tibia Bone Characteristics Displayed Inmentioning
confidence: 62%
See 2 more Smart Citations